До питання про генезис відповідальності за злочини проти осіб та установ, які мають міжнародний захист - Ральченко, І. М.; Ralchenko, I. M. (Право і безпека. - 2015. - № 3 (58). - С. 93–97., 2015)
Розглянуто розвиток принципу посиленого захисту осіб, які представляють суб’єктів міжнародного права, з найдавніших часів і до новітнього періоду розвитку міжнародного права й національного кримінального законодавства. Встановлено зв’язки заборони вчинення злочинів проти осіб та установ, що мають міжнародний захист, з інститутом гостинності та принципами права міжнародних зносин. Визначено періоди розвитку кримінального законодавства України, коли були здійснені спроби встановлення відповідальності за злочини проти осіб та установ, які мають міжнародний захист.

The relevance of the topic is determined by the need to continue developing mechanisms of protection by means of national (domestic) criminal law, international rule of law and persons who represent the subjects of international law. The article’s objective is to study the genesis of criminal liability for crimes against persons and institutions that have international protection. The work is made by using historical, historical and legal methods and system and structural approach. The development of the principle of enhanced protection of persons who represent the subjects of international law is considered from ancient times to the modern period of development of international law and national criminal legislation. Relations of prohibition of committing crimes against persons and institutions that have international protection with the institution of hospitality, as well as with the principles of law of international relations are established. It is noted that the greatest influence on the formation of special prohibitions on the attacks on functionaries in the field of international and legal relations have committed principles developed to ensure diplomatic activity. Provisions of monuments of domestic law, criminal and legal acts that were in force in the period from the XVIII to XXI century have been analyzed. The stages of the development of criminal legislation of Ukraine are defined, when there were attempt to establish liability for the crimes against persons and institutions that have international protection. Conducted analysis allowed to state that the provisions of the Art. 444 of the Criminal Code of Ukraine is a legal novelty that requires further research.

Рассмотрено развитие принципа усиленной защиты лиц, представляющих субъектов международного права, с древнейших времён и до новейшего периода развития международного права и национального уголовного законодательства. Установлены связи запрета совершения преступлений против лиц и учреждений, имеющих международную защиту, с институтом гостеприимства и принципами права международных отношений. Определены периоды развития уголовного законодательства Украины, когда были предприняты попытки установления ответственности за преступления против лиц и учреждений, имеющих международную защиту.
Ralchenko, I.M. (2015), “On the issue about the genesis of liability for crimes against persons and institutions having international protection” [“Do pytannia pro henezys vidpovidalnosti za zlochyny proty osib ta ustanov, yaki maiut mizhnarodnyi zakhyst”], Pravo i Bezpeka, No. 3, pp. 93–97.
Ральченко, І. М. До питання про генезис відповідальності за злочини проти осіб та установ, які мають міжнародний захист // Право і безпека. - 2015. - № 3 (58). - С. 93–97.
Keywords: Кримінальне право. Criminal Law. Уголовное право; Міжнародне право .International Law. Международное право; Наукові публікації. Scientific publications. Научные публикации; злочини проти осіб та установ, що мають міжнародний захист; кримінальна відповідальність; міжнародний правопорядок; дипломатична недоторканність; crimes against persons and institutions that have international protection; criminal liability; international rule of law; diplomatic immunity; преступления против лиц и учреждений, имеющих международную защиту; уголовная ответственность; международный правопорядок; дипломатическая неприкосновенность